Age for Leisure? Political Mediation and the Impact of the Pension Movement on U.S. Old-Age Policy - Amenta, Edwin; Caren, Neal; Olasky, Sheera Joy (American Sociological Review, 2005)
This article elaborates a political mediation theory of the impact of social movements on states and policy, positing that the influence of mobilization and specific strategies of collective action depends on specified political contexts and the type of influence sought. Examining the influence of the U.S. old-age pension movement, which involved millions of people, this article appraises the mediation model using state-level data from the 1930s and 1940s on Old Age Assistance—the main support for the aged at the time-and a Senate vote for generous senior citizens' pensions in 1939. Our models control for other potential influences, notably public opinion, which is often ignored in empirical studies and sometimes claimed to be responsible for causal influence mistakenly attributed to challengers. We employ pooled cross-sectional and time series analyses and fuzzy set qualitative comparative analysis (FSQCA), which is especially suited to appraising the combinational expectations of the political mediation model. Both sets of analyses show that the pension movement was directly influential on the outcomes and provide support for the political mediation arguments.